Implementation of the Qudwah Hasanah Method in Strengthening Moral Values in Learning Akidah Akhlak at MIS. At-Tahzib Related to the 2025/2026 Academic Year - M. Rofhan Zuhdan; Ridwan Ridwan; Lalu Asriadi (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This study aims to describe how the qudwah hasanah method is applied in strengthening moral values in the learning of Akidah Akhlak of fifth-grade students at MIS Attahzib Kekait, while also revealing various obstacles that arise during the implementation process. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation studies. Research informants include the principal, fifth-grade Akidah Akhlak teachers, and fifth-grade students of MIS Attahzib Kekait in the 2025/2026 academic year. The data analysis process is carried out systematically through the stages of data reduction, data presentation, and drawing conclusions by referring to the Miles and Huberman model. The results of the study indicate that the implementation of the qudwah hasanah method takes place through five inter-integrated stages, namely educator self-readiness, direct role modeling, delivery of simulations and advice, habituation accompanied by supervision, and evaluation and reinforcement. Through this process, the moral values that develop in students include individual moral aspects such as honesty, discipline, and responsibility; social morals such as politeness, empathy, and cooperation; and religious morals reflected in the habit of praying, reading the Quran, and consistently performing religious duties. However, the implementation of this method still faces several obstacles, including the influence of the family environment, low awareness of the importance of moral values among some students, limited learning time, the recurrence of deviant behavior, and suboptimal coordination between teachers. Therefore, this study emphasizes the importance of ongoing collaboration between schools, families, and the entire school community so that the implementation of the Qudwah Hasanah method can run more effectively and provide maximum impact.